ALMA spectrum of the extreme OH/IR star OH 26.5+0.6. Issue Volume 14:Issue S343(2019) (August 2018) - Justtanont, K.; Muller, S.; Barlow, M. J.; Engels, D.; García-Hernández, D. A.; Groenewegen, M. A. T.; Matsuura, M.; Olofsson, H.; Teyssier, D.; Marti-Vidal, I.; Khouri, T.; Van de Sande, M.; et al.
Abstract: We present ALMA band 7 data of the extreme OH/IR star, OH 26.5+0.6. In addition to lines of CO and its isotopologues, the circumstellar envelope also exhibits a number of emission lines due to metal-containing molecules, e.g., NaCl and KCl. A lack of C 18 O is expected, but a non-detection of C 17 O is puzzling given the strengths of H2 17 O in Herschel spectra of the star. However, a line associated with Si 17 O is detected. We also report a tentative detection of a gas-phase emission line of MgS. The ALMA spectrum of this object reveals intriguing features which may be used to investigate chemical processes and dust formation during a high mass-loss phase.